From mitochondria to heart: the role and challenges of mitochondrial antiviral signaling protein in cardiovascular disease - Jiang, Mengting; Huang, Runze; Li, Wei (Frontiers in Cardiovascular Medicine, 2025)
Mitochondrial Antiviral Signaling Protein (MAVS) is a pivotal adaptor protein in the innate immune response, mediating the activation of NF-κB and type I interferon signaling pathways during viral infections. As an integral component of the mitochondrial outer membrane, MAVS also plays critical roles in the regulation of apoptosis, cellular metabolism, and the activation of inflammasomes, including NLRP3 and caspase family members. Emerging evidence indicates that MAVS is not only essential in antiviral defense but also contributes significantly to the pathogenesis of various diseases, notably cardiovascular diseases. In this review, we provide a comprehensive overview of the molecular structure of MAVS and the regulatory mechanisms modulating its activity. We further highlight the involvement of MAVS in the development of cardiovascular diseases through its participation in innate immune signaling and mitochondrial dynamics. Particular attention is given to the regulation of MAVS by post-translational modifications—such as ubiquitination, methylation, and acetylation—as well as by microRNAs and other mitochondria-associated proteins. These insights aim to deepen the understanding of MAVS as a potential biomarker and therapeutic target, offering novel perspectives for the prevention, diagnosis, and immunotherapeutic intervention of cardiovascular diseases.